PENGEMBANGAN PERANGKAT PEMBELAJARAN PADA MATERI POKOK SISTEM PERSAMAAN LINEAR TIGA VARIABEL DI KELAS X MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING - Silvia Yohana Sitanggang; Zulkarnain Zulkarnain Zulkarnain; Elfis Suanto Suanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was conducted due to limited mathematics learning devices that use learning approaches and models that can support learning in the 2013 curriculum. This research aims to produce mathematic learning instruments like syllabus, lesson plan (LP), and student worksheet (SW) in the material Linear Equation System of Three Variables in class X which applies valid and practical Problem Based Learning models. The development model used is 4-D model that consist of define, design, development and disseminate, but disseminate didn’t do because this purpose of study just produce devices which valid and practicality and got it on development step. The research instruments used were learning device validation sheets, teacher response questionnaires and student response questionnaires. Devices compiled was validated by three validators and revised based on the suggestions of validators. Based on the result of data analysis shows average score for syllabus are 3,71, LP are 3.83, and SW are 3.68 from the 4,00 scale, so the resulting devices is categorized as very valid. Device was valeted then tested a large group with subjects 33 students of class X Accounting-1 state vocational high school Labor Pekanbaru using LP and SW. The results of data analysis on practicality of learning devices by the teacher and the practicality of SW by students is 94.22% which is categorized as very practical. Key Words: Learning Devices, Problem Based Learning, Validity and Practicality